Dehydration does not drive host behavioural manipulation by hairworms - Louise M. Coates; Kieran Reynolds; Mara Carey-Wood; Dominika Lastik; Chris Vennard; Jean-François Doherty; Eddy Dowle; Benjamin J. Matthews; Leonard J. Foster; Stuart E. Reynolds; Vicky L. Hunt (PLoS ONE, 2025)
Nematomorphs are parasitic worms of arthropods, which complete their life cycle via behavioural manipulation of their host so that they can enter water to find a mate. Although this behaviour is readily observed, the underlying mechanism is largely unknown; previously proposed hypotheses include an attraction to polarised light, increased erratic behaviour and dehydration-driven behaviour. Here, we investigated the ‘Dehydration Hypothesis’, which posits that nematomorphs either induce dehydration or mimic dehydration through biosynthetic changes to stimulate host water-seeking behaviour. House crickets, Acheta domesticus, were experimentally deprived of water and their behaviour compared to crickets infected with the nematomorph Paragordius varius. Both infected and dehydrated crickets were more likely to interact with water than uninfected, hydrated crickets. However, dehydrated crickets preferred to submerge their heads in the water compared to infected crickets which preferred to fully enter the water. Quantitative mass spectrometry of cricket haemolymph identified unique proteomic signatures of infection (27 differentially abundant proteins, infected cf. control) and dehydration (17 differentially abundant proteins, dehydrated cf. control). Our results indicate that dehydration is not a strong driving mechanism for behavioural manipulation by nematomorphs, but nevertheless infected and dehydrated share the increased tendency of dehydrated crickets to interact with water. Our data also provide new insights into the proteomic response during nematomorph infection. Notably, we observed a decrease in the cricket egg yolk protein vitellogenin and the carbohydrate digestion enzyme α-amylase, and an increase in abundance of the immune related hemocyanin protein family.